Biocontrol of Mycotoxigenic Fungi by Actinobacteria - Louise Maud; Nathalie Barakat; Julie Bornot; Selma P. Snini; Florence Mathieu (Journal of Fungi)
Actinobacteria are well known for their production of metabolites of interest. They have been previously studied to identify new antibiotics in medical research and for their ability to stimulate plant growth in agronomic research. Actinobacteria represents a real source of potential biocontrol agents (BCAs) today. With the aim of reducing the use of phytosanitary products by 50% with the different Ecophyto plans, a possible application is the fight against mycotoxin-producing fungi in food matrices and crops using BCAs. To deal with this problem, the use of actinobacteria, notably belonging to the Streptomyces genus, or their specialized metabolites seems to be a solution. In this review, we focused on the impact of actinobacteria or their metabolites on the development of mycotoxigenic fungi and mycotoxin production on the one hand, and on the other hand on their ability to detoxify food matrices contaminated by mycotoxins.